(untitled) (Research, Society and Development, 2019)
This article presents an activity developed with the use of a technological tool called Kahoot to teach Portuguese that proposes an alternative to evaluate and guide parameters of knowledge of the contents intended for students in the 6th grade of elementary school. This activity was developed in a private school located in the east part of the city of São Paulo. In this paper, it has been made known that this resource may be an option to gamify the class and thus establish patterns of competition among the students involved in the activity. What establishes the theoretical basis of paper is the Activity Theory (AT), which brings elements for an analysis of how the interaction can foster and enhance the pedagogical value in the teaching process of Portuguese and its concepts in a dynamic and participatory way in the collaborative learning among them.